1999
DOI: 10.1046/j.1472-765x.1999.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disk rotational speed on heavy metal accumulation by rotating biological contactor (RBC) biofilms

Abstract: S. 1999. The efficiency of a rotating biological contactor (RBC) in the treatment of waters contaminated with cadmium, copper and zinc, in particular the effect of rotational speed, namely 3, 15 and 25 rev min −1 , on heavy metal reclamation was evaluated. Atomic absorption spectrophotometric analysis indicated × 92% and ³ 20% removal of copper (Cu 2+ ) and zinc (Zn 2+ ), respectively. Cadmium (Cd 2+ ) levels, however, remained constant. Similar results were obtained at all three rotation speeds tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The efficiency of various biosorption systems reported in the scientific literature for metal removal are highly variable and difficult to compare (Akhtar et al 2008;Bayramoglu et al 2006;Costley and Wallis 1999, 2001aDvorak et al 1992). As it was mentioned previously, the mechanism of metal biosorption is a complicated process and depends on a variety of factors including the ambient and environmental conditions such as pH and temperature; the initial concentration of metal ions and biomass; and competition of ions for biding sites (Das et al 2009a, b;Lottermoser et al 1999;Mathure and Patwardhan 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of various biosorption systems reported in the scientific literature for metal removal are highly variable and difficult to compare (Akhtar et al 2008;Bayramoglu et al 2006;Costley and Wallis 1999, 2001aDvorak et al 1992). As it was mentioned previously, the mechanism of metal biosorption is a complicated process and depends on a variety of factors including the ambient and environmental conditions such as pH and temperature; the initial concentration of metal ions and biomass; and competition of ions for biding sites (Das et al 2009a, b;Lottermoser et al 1999;Mathure and Patwardhan 2005).…”
Section: Discussionmentioning
confidence: 99%
“…High interfacial areas generated by the discs, simple and feasible design and operation, low land occupancy, low energy consumption, low cost of operation and maintenance, high reaction rate and treatment efficiency are the principal advantages of this type of reactor (Cortez et al 2008;Mathure and Patwardhan 2005). A number of studies reported the metal removal capacity of immobilised live microorganisms in a batch or continous systems using different type of reactors included rotary systems such as RBCs, with only one to three cations in solution (Akhtar et al 2008;Bayramoglu et al 2006;Travieso et al 2002;Costley and Wallis 1999, 2001aGyure et al 1987). A previous review (Malik 2004) stated that these biotreatment studies that demonstrated high efficiency for metal removal did not perform well in field trials.…”
Section: Introductionmentioning
confidence: 99%
“…112 The ability of modified Slovak zeolites to collect Cr III was measured by FAAS. 113 In the determination of Fe by FAAS 114 preconcentration by co-flotation with lead hexamethylenedithiocarbamate gave an LOD of 0.3 mg l 21 . A variety of electrode materials were able to preconcentrate Cd and Cu 115 to an extent comparable to that obtained with complexing agents (8-hydroxyquinoline, dithizone and rubeanic acid immobilized on filter paper).…”
Section: Preconcentrationmentioning
confidence: 99%